2022
DOI: 10.3390/su15010536
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sustainable and Environment Friendly Growing Media Composition for Pot Mum (Chrysanthemum morifolium Ramat.)

Abstract: The use of different growing media offers a valuable alternative to the conventional use of soil for quality flower production due to their good water holding capacity, aeration and nutrient status. The experiment was conducted in a Completely Randomised Design with three replications in the years 2021–2022 to study the influence of different compositions of growing media [Soil, Sand, Vermicompost, Cocopeat, Vermiculite, Perlite and Leaf mould] in different ratios on the growth and development of pot mum (Chry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, many previous studies conducted on different species of bougainvillea have shown that significantly better results were observed for root and shoot parameters at higher concentrations of IBA than in the present experiment (Parmar et al, 2010;Singh et al, 2011;Asl et al, 2012;Kuldeep et al, 2013). The strong shoot and root inducing capacity of Rootex C and IBA (1000 mg L -1 ) combining with acceptable pH, electrical conductivity and other physical (lower bulk density, good aeration, good water holding capacity) and chemical properties of sand and cocopeat media (Krishnapillai et al, 2020;Singh et al, 2022) hastened the overall performance of bougainvillea cuttings.…”
Section: Discussionmentioning
confidence: 99%
“…However, many previous studies conducted on different species of bougainvillea have shown that significantly better results were observed for root and shoot parameters at higher concentrations of IBA than in the present experiment (Parmar et al, 2010;Singh et al, 2011;Asl et al, 2012;Kuldeep et al, 2013). The strong shoot and root inducing capacity of Rootex C and IBA (1000 mg L -1 ) combining with acceptable pH, electrical conductivity and other physical (lower bulk density, good aeration, good water holding capacity) and chemical properties of sand and cocopeat media (Krishnapillai et al, 2020;Singh et al, 2022) hastened the overall performance of bougainvillea cuttings.…”
Section: Discussionmentioning
confidence: 99%
“…The Impatiens plant could produce more root dry weights when cultivated in a medium featuring elevated nutrient status combined with higher moisture content (Kazemi et al, 2020). This outcome can be attributed to the significant influence of root growth on nutrient uptake (Singh et al, 2023). Additionally, the allocation of assimilates within the plant further supports the growth in stem diameter and leaves number (Lojo et al, 2019).…”
Section: Assimilate Partitioningmentioning
confidence: 98%
“…The different growth medium offers quality plant production due to their good water-holding capacity, aeration and nutrient status (Singh et al, 2023), although their effectiveness can be influenced by genotype, environment and production management (Francini and Sebastiani, 2019). In Indonesia and other tropical regions, the cocopeat medium stands out as a widely accessible option (Ayu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ideal plantgrowing medium can sustain plant life, requires little input, and is not easily damaged (Graceson et al 2013). Chaff charcoal is light in weight but has less waterholding capacity (Singh et al 2022). In contrast, clay, sand, and topsoil have good physical attributes for plant growth but are heavy, especially in water-saturated conditions, and are prone to waterlogging (Sodiq et al 2019).…”
Section: Response Of Mint Cuttings To Auxin and Mediamentioning
confidence: 99%